Tradisi Larungan Di Telaga Ngebel Perspektif Islam - Ambar Wahyu Harinayuetik (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
Tradition is a heritage in the form of culture from our ancestors, which has been lived for hundreds of years and is still carried out by their descendants. Whereas culture is something that is passed down not through genes but through a process of learning, experience, or instructions from parents, elders, neighbors, or certain communities. In Islam, traditions that do not violate Islamic law can be accepted and traditions that are not in accordance with religious law can be carried out by Islamization between tradition and culture. The method used in this research is a qualitative method. The tradition of offering offerings is intended so that this can keep Ngebel away from all calamities and disasters. The tradition of larung offerings had changed its name to larung treatise do'a because there were several parties who disagreed, so it was changed back to the ceremony of larungan 1 suro telaga ngebel. This ceremony is held at Ngebel lake, by slaughtering a kendhit goat. The head of the kendhit goat is planted on the lake pier, its feet are planted in the four corners of the lake, the other offerings are planted in grass, and the meat is distributed to local residents.